أكتب بتمازيغت ‏تيفيناغ - أبو زخار, فتحي سالم (‏المركز الليبي للدراسات الأمازيغية, 2019)
Keywords: Enseignement – Djebel Nefousa; Linguistique – Djebel Nefousa

Noun Prefixes in Eastern Berber - Van Putten, Marijn (Rivista degli studi orientali, 2015)
The Eastern Berber languages have a noun prefix system different from other Berber languages. They undergo shortening of the prefix in contexts not found elsewhere and tje feminine plural prefix ti- appears to be absent. This article examines the conditioning of the different allomorphs of the prefixes, and suggests that the absence of the plural prefix ti- cannot be explained as the result of a internal historical development, which may suggest that the Eastern Berber feminine plural prefix tə- is the original form.
Keywords: Linguistique – Djebel Nefousa

A Grammar of Awjila Berber (Libya) based on Umberto Paradisi’s Material - Van Putten, Marijn (Leiden University, 2013)
Keywords: Linguistique – Djebel Nefousa

Lingue e letterature berbere di Libia dall’epoca coloniale agli eventi di questi giorni: continuità e innovazioni - Brugnatelli, Vermondo (Università degli Studi di Milano - Bicocca, 2011)
1. Una lettera di Chemmakhi a Motylinski (22 novembre 1881) 2. Madghis e Mazigh Buzakhar
Keywords: Linguistique – Djebel Nefousa

Corrections au « Glossaire de la Mudawwana » publié par Bossoutrot - Brugnatelli, Vermondo (2016)
Keywords: Linguistique – Djebel Nefousa

Autour d’un glossaire arabo-berbère du Moyen-Age (‘Dialecte du Djebel Nefoussa’) - Naït-Zerrad, Kamal (La Lingua nella Vita e la vita della lingua : Itinerari e percorsi degli studi berberi. Miscellanea per il Centenario di studi berberi a "L'orientale" di Napoi Scritti in onore di Francesco Beguinot, 2015)
Keywords: Linguistique – Djebel Nefousa

Some grammatical features of ancient eastern Berber (the language of the Mudawwana) - Brugnatelli, Vermondo (He bitaney lagge: studies on language and African linguistics in honour of Marcello Lamberti, 2011)
MSS containing parts of [the Berber translation of] al-Mudawwana: 1) a MS found in a French library, that had been in the possession of Motylinski and Bossoutrot; it contains 594 pp. and covers 9 chapters out of 16 (see Umādī 2006c); 2) a MS bought from a bookseller, 394 pp. and 7 chapters (see Ould-Braham 2008, 2009); 3) the reproduction of a MS located by Brugnatelli in a Tunisian library, containing 896 pp. and 14 chapters, bearing the title of K. al-Barbariyya.
Keywords: Linguistique – Djebel Nefousa

Il sistema preposizionale del berbero nefûsi di Fassâto - Pennachietti, Fabrizio ("Parcours berbères": mélanges offerts à Paulette Galand-Pernet et Lionel Galand pour leur 90e anniversaire, 2011)
Keywords: Linguistique – Djebel Nefousa

The Problems Encounter Teachers in Teaching Translation: Case Study Nafousa Mountain University Libya - Hammad, Suad Arebi (جامعة أم درمان الاسلامية, 2013)
Keywords: Linguistique – Djebel Nefousa

L'arabe de Žâdū (Žébel Nefûsa) d'après Gioia Chiauzzi - Pereira, Christophe (Dynamiques langagières en Arabophonies: variations, contacts, migrations et créations artistique ; hommage offert à Dominique Caubet par ses elèves et collègues, 2012)
Keywords: Linguistique – Djebel Nefousa

The Original Format of Abū Ghānim’s Mudawwana: Philological Evidence from a Berber Commentary - Brugnatelli, Vermondo (Today's perspectives on Ibadi history, 2017)
Since the remarkably strong increase in scholarly activity concerning research on the Ibadiyya in the recent decades it is high time to provide insight into the topical state of affairs. The present volume is devoted in particular to the study of Ibadi history and its sources, thus covering the long period of time from early Islam to our days, and extending geographically from the Indian Ocean region to the Mediterranean. Scholars from all over the world deal in their contributions to this volume with a great variety of topics and approaches, thereby revealing in several respects the challenging character of this field of research, just to mention the question of regional specifics and interrelations of the dispersed Ibadi community, the filling of information gaps in its historical narrative, or the reconstruction of sources and their appropriate interpretation. In that way this book also may serve as an ample source of inspiration to future research on Ibadi history
Keywords: Linguistique – Djebel Nefousa

Nefoussa : Langue et révolution. (Témoignage) - Ferkal, Masin (Encyclopédie berbère, 2012)
Number: 33 Publisher: Éditions Peeters
Keywords: Linguistique – Djebel Nefousa

Nefoussa : Langue - Naït-Zerrad, Kamal (Encyclopédie berbère, 2012)
Keywords: Linguistique – Djebel Nefousa

Reflexes of the proto-Berber glottal stop in Nefusa and Ghadames - Van Putten, Marijn (Wiener Zeitschrift für die Kunde des Morgenlandes, 2015)
Keywords: Linguistique – Djebel Nefousa

Jespersen’s Cycle in Libyan Arabic and Nafusi Berber - Ghadghoud, Khawla (University of Manchester, 2013)
Keywords: Linguistique – Djebel Nefousa

Un témoin manuscrit de la « Mudawwana d’Abū Ġānim » en berbère - Brugnatelli, Vermondo (Études et Documents Berbères, 2016)
Keywords: Fiqh – Libye – 8e siècle; Linguistique – Djebel Nefousa

Arab-Berber contacts in the Middle Ages and ancient Arabic dialects: new evidence from an old Ibāḍite religious text - Brugnatelli, Vermondo (African Arabic: Approaches to Dialectology, 2013)
L’analyse d’un long manuscrit contenant un texte arabo-berbère du Moyen Âge, le Kitāb al- barbariyya, connu aussi sous le nom de Moudaououana d’Ibn R’anem (Motylinski et Bossoutrot) ou Mudawwana d’Abû Ġânim al-Ḫurâsânî (Ould-Braham et U-Madi), permet de relever quelques phénomènes liés au contact linguistique entre le berbère et l’arabe du Moyen Âge. La date de composition du texte n’est pas connue mais elle remonte à une époque assez reculée (entre le 10ème et le 15ème siècle). Plusieurs indices (entre autres, l’orthographe du son [g], transcrit avec <ǧ> et pas avec <q>) font penser à une période antérieure ou très proche de l’invasion hilalienne. Parmi les phénomènes observables, on notera : - d’un côté les emprunts du berbère à l’arabe, qui sont concentrés surtout dans le domaine de la religion, même si la langue du document préserve beaucoup de lexique indigène. Dans quelques cas, on peut constater une évolution dans l’utilisation des emprunts d’un livre à l’autre à l’intérieur de l’ouvrage, probablement en raison d’une différence d’époque de composition des différentes parties ; - de l’autre côté, dans certains cas, comme les noms de nombre de la deuxième dizaine, la forme de l’emprunt démontre une évolution déjà avancée de la langue arabe parlée au Maghreb par rapport à la langue « classique ».
Keywords: Linguistique – Djebel Nefousa